The Relationship of Dietary Knowledge Level and Blood Sugar Levels in Type 2 Diabetes Mellitus Patients - Wiji Rismawati; Okti Sri Purwanti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Type 2 diabetes mellitus patients often do not understand a balanced diet. This lack of knowledge has an impact on the high blood sugar of patients with type 2 diabetes mellitus. This study aims to analyze the relationship between dietary knowledge and blood sugar levels in patients with type 2 diabetes mellitus. This study used a quantitative approach with a cross-sectional design and applied the total sampling method, involving 40 respondents who were patients with type 2 diabetes mellitus at the Kartasura Health Center. This study was conducted in December 2024-January 2025. Data collection was carried out by distributing questionnaires to respondents who conducted examinations at the Kartasura Health Center Prolanis Clinic. Pearson test was used for data analysis because the data distribution was normal. The results of the Pearson statistical test on type 2 diabetes mellitus patients at the Kartasura Health Center showed a p-value = 0.001. The results revealed a relationship between dietary knowledge and blood sugar levels in patients with type 2 diabetes mellitus at the Kartasura Community Health Center. Researchers suggest exploring other variables that affect blood sugar levels, such as physical activity, and diet. Qualitative research methods can also be used to investigate patients taking routine medication and the influence of the surrounding environment, allowing for more generalized findings.